2014
DOI: 10.5430/wje.v4n6p16
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Vocabulary Learning Strategy Use of Turkish EFL Learners in Relation to Academic Success and Vocabulary Size

Abstract: The purpose of this study was to investigate Vocabulary Learning Strategy (VLS) use of English Language and Literature Department students in relation to academic success and vocabulary size. The participants of the study are 213 English Language and Literature students. Two data collection tools were used in the study. The first tool was theVocabulary Learning Strategy (VLS) questionnaire which was adapted from by Gu & Johnson (1996), and the second data collection tool was a Vocabulary Level Test (VLT) devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…Some research to find their relationship with vocabulary size focusing on EFL undergraduate and graduate students was conducted by Ali & Kalajahi (2012); Hamzah, Kafipour, & Abdullah (2009); and Kırmızı (2014). All those studies seemed to reveal almost similar results showing that some categories of Vocabulary Learning Strategies contribute significantly to the students' vocabulary size despite their different level of significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research to find their relationship with vocabulary size focusing on EFL undergraduate and graduate students was conducted by Ali & Kalajahi (2012); Hamzah, Kafipour, & Abdullah (2009); and Kırmızı (2014). All those studies seemed to reveal almost similar results showing that some categories of Vocabulary Learning Strategies contribute significantly to the students' vocabulary size despite their different level of significance.…”
Section: Introductionmentioning
confidence: 99%
“…However, a deep explanation on how Vocabulary Learning Strategies relate to vocabulary knowledge especially in its certain aspects such as learner's knowledge of affixes, their vocabulary size, and words association has not been explored enough (Nosidlak, 2013). Some research to find their relationship with vocabulary size focusing on EFL undergraduate and graduate students was conducted by Ali & Kalajahi (2012); Hamzah, Kafipour, & Abdullah (2009); and Kırmızı (2014). All those studies seemed to reveal almost similar results showing that some categories of Vocabulary Learning Strategies contribute significantly to the students' vocabulary size despite their different level of significance.…”
Section: Introductionmentioning
confidence: 99%
“…However, VLS preferences were not found to be consistent with the proficiency level. Kırmızı (2014) investigated 213 English language and literature students' use of VLS by using a vocabulary learning strategy questionnaire and vocabulary levels test and found that the participants had a high level of vocabulary size for 2000 word level, 3000 word level, and academic word levels, a moderate level of vocabulary size for 5000 word level and a low level in 10000 word level. It was also found in the study that the participants had a moderate level of vocabulary learning strategy use.…”
Section: Studies On Vocabulary Learning Strategiesmentioning
confidence: 99%
“…There are various studies in the literature that are focused on determining vocabulary learning strategies of foreign language learners (Bekleyen, 2005;Çelik & Toptaş, 2010;Çelikkaya, 2012;Engin, Dikbayır, & Genç, 2017;Gömleksiz, 2013;Hişmanoğlu & Turan, 2019;Kırmızı, 2014;Kırmızı & Topcu, 2014;Noprianto & Purnawarman, 2019;Tanyer & Ozturk, 2014). There are also studies that examine strategy use of TFL learners in terms of language learning strategies (Alyılmaz & Şengül, 2017;Akın & Çetin, 2016;Barut, 2015;Boylu, 2015;Bölükbaş, 2013;Şengül, 2012;Varışoğlu, 2017).…”
Section: Introductionmentioning
confidence: 99%